2018
DOI: 10.1589/jpts.30.448
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of the effectiveness of ESWT and ultrasound treatments in myofascial pain syndrome: randomized, sham-controlled study

Abstract: [Purpose] The purpose of this study is to compare effectiveness of extracorporeal shock wave therapy (ESWT), ultrasound (US) and sham ESWT in the treatment of myofascial pain syndrome (MPS). [Subjects and Methods] Sixty MPS patients aged 18–60 years were included in the study. The patients were randomized equally into 3 groups. Group 1 received ESWT for 4 session with 3 day-intervals. Group 2 received 4 sessions of sham ESWT. US was applied to Group 3 for 10 sessions. All patients were recommended an exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 20 publications
(24 reference statements)
3
16
0
1
Order By: Relevance
“…The encounter between the next emitted wave and the reflected wave generates a secondary wave of greater intensity than the incident wave [19]. Thus, increasing the frequency of pulse firing increases the number of these secondary waves, resulting in a greater number of cavitations [20,23] and thus a greater therapeutic effect, precisely in the areas related to pain and analgesia, explaining the fact that the higher frequency used in our study increased the magnitude of the analgesic effect in comparison with that obtained with low frequencies by other authors [51,52].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The encounter between the next emitted wave and the reflected wave generates a secondary wave of greater intensity than the incident wave [19]. Thus, increasing the frequency of pulse firing increases the number of these secondary waves, resulting in a greater number of cavitations [20,23] and thus a greater therapeutic effect, precisely in the areas related to pain and analgesia, explaining the fact that the higher frequency used in our study increased the magnitude of the analgesic effect in comparison with that obtained with low frequencies by other authors [51,52].…”
Section: Discussionsupporting
confidence: 60%
“…A study comparing rESWT with therapeutic ultrasound showed that four sessions of rESWT at 2,000-3,000 pulses/session, a pressure of 1.60-3.00 bars, and a frequency of 10 Hz reduced the VAS score by 15.3 mm, compared with only 10.7 mm for therapeutic ultrasound [51]. In another study, involving patients with shoulder tendinitis, seven sessions of rESWT, with a mean pressure of 1.70 bar, mean frequency of 5 Hz, and mean of 2,175 pulses/session, resulted in a 26 mm reduction in the VAS score [52].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that three sessions of therapy improved pain compared to a single-session therapy. Consistent with these findings, Akturk et al 29 divided 60 MPS patients into three groups and used L-ESWT for four sessions. They found a statistically significant improvement in pain and SF-36 subscale scores in the ESWT and US groups; however, there was no statistically significant difference in the anxiety and depression scores after treatment.…”
Section: Discussionmentioning
confidence: 80%
“…The effectiveness of US and SWs has been compared in pathologies such as fibromyalgia/myofascial pain syndrome [ 20 ], plantar fasciitis [ 21 , 22 ], epicondylitis [ 23 , 24 ], and tendonitis of the shoulder [ 25 ], and no significant differences were noted in terms of alleviating pain, increasing the quality of life (using the short form-36 (SF-36)), or improving disability. In our paper, we aim to measure the effectiveness of these two treatment modalities in terms of improving the pain, disability, and quality of life in adult patients with idiopathic scoliosis.…”
Section: Introductionmentioning
confidence: 99%